CLASSIFICATION OF VOCATIONAL HIGH SCHOOL GRADUATES' ABILITY IN INDUSTRY USING EXTREME GRADIENT BOOSTING (XGBOOST), RANDOM FOREST, AND LOGISTIC REGRESSION - Agustiningsih, Afikah; Findawati, Yulian; Alnarus Kautsar, Irwan (Informatika, Universitas Jenderal Soedirman, 2023)
The education world is one of the main sources in producing Human Resources. Vocational High School (SMK) is one level of school that presents various majors that are ready to compete in the industrial world. Therefore, a school institution needs to have a system to determine the quality of education provided to students so that they can compete in the industrial world. This study designs a system that is capable of classifying SMK student graduates as an evaluation for the school institution. The goal is to enable the school to devise strategies for producing better student quality in the following year. There are four classes in this study, namely those who work, those who are not working yet, those who are in college, and those who are entrepreneurs. There are several stages in building the classification system, including pre-processing, processing, and evaluation. This research uses three machine learning algorithms, namely XGBoost, Random Forest, and Logistic Regression. The results of the three methods obtained a training score of 91.70%, a test score of 66.88%, and an accuracy score of 67% generated by the XGBoost algorithm. The Random Forest algorithm produced a training score of 97.36%, a test score of 68.71%, and an accuracy score of 67%. Meanwhile, Logistic Regression produced a training score of 51.14%, a test score of 50.43%, and an accuracy score of 50%.